Age and reasons for first dental visit among children in Lagos, Nigeria - Olatosi, Olubukola; Onyejaka, Nneka; Oyapero, Afolabi; Ashaolu, Joseph; Abe, Adesuwa (The Nigerian postgraduate medical journal, 2019)
Background: An early first dental clinic appointment offers the prospect of prompt preventative care and parental education regarding the oral health of the child. The evidence-based recommendation by dental professionals all over the world is that a child should visit a dentist before or by 1 year of age. Aim: This study aimed to determine the chronological age at and the purpose for a first dental clinic visit amongst children aged 16 years and below attending the Paediatric Dental Clinic at the Lagos University Teaching Hospital (LUTH). Materials and Methods: This was a retrospective study conducted amongst children who attended the Paediatric Dental Clinic at the LUTH between January 2017 and December 2018. Data on age at first dental visit, reasons for attending and other information relevant to the study were collected. Descriptive statistics and Chi-square analysis were conducted, and the level of significance was set at P < 0.05. Results: A total of 1157 children were studied, comprising 580 (50.5%) males and 577 (49.9%) females. Their mean age on their first dental visit was 7.9 ± 3.7 years. Most of the children (31.4%) had their first dental visits at 7 and 9 years, and 0.8% of the children had their first dental visit below the age of 1 year. The most common reason for visiting the dental clinic was dental pain (33.1%). A higher proportion of the children (911 [79.0%]) had their first dental visit for therapeutic purposes, whereas 246 (21.0%) children visited the dental clinic for preventive care. Sex and age at first dental visit were statistically significantly associated with the reason for attendance (P < 0.001). Conclusion: Most children had their first dental visit between the ages of 7 and 9 years, mainly because of pain. It is necessary to create more awareness among parents/caregivers and to establish the concept of dental home.